Pengaruh Metode Ummi terhadap Kemampuan Bacaan Al-Quran di TPQ Al-Hidayah Desa Tanjung Rasa - Ayu Nurtoriqoh; Eka Hujaemah; Indah Sartika Putri; Neneng Maemunah; Yani Nurbayani; Hilma Mega Farha (Journal on Education, 2024)
This research was conducted because there are institutional programs to help achieve success in the ability to read the Qur'an, so there is a need for a Qur'an teaching system that can guarantee that every student who graduates from the institution can read the Qur'an. The aim of this research is to analyze whether the ummi method has an influence on students' learning in reading the Qur'an. This type of research is quantitative research and the type of research is correlational research. The results of this research can be summarized in three ways, namely: The application of the ummi method at TPQ Al-Hidayah Tanjung Rasa Village with a questionnaire result of a score of 20. With a score classified as good, the value of the Al-Quran Reading Ability of TPQ Al-Hidayah students in Tanjung Rasa Village is proven by the results The test shows that this value is classified as good, the influence of the ummi application method on the ability to read the Al-Quran of students at TPQ Al-Hidayah, Tanjung Rasa Village. The conclusion that can be drawn from this research is that there is an insignificant value with a significant value of 0.719 < 0.05